Frameworks for Protecting Workers and the Public from Inhalation Hazards - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Individuals in the United States and Americans abroad are exposed to inhalation hazards from a variety of sources, and these hazards can have both short- and long-term adverse effects on health. For example, exposure to wildfire smoke, which contains particulate matter and toxic chemicals, can lead to respiratory problems, increased risk for heart attacks, and other adverse health outcomes. Individuals also may be exposed to airborne infectious agents through aerosol or droplet transmission, and as demonstrated by the COVID-19 pandemic, the individual and public health consequences of these exposures can be severe. Storms, floods, and hurricanes can increase exposure to moisture-driven hazards, such as mold, and to accidental releases from production facilities or transport vehicles that may result in chemical exposures. The current regulatory system is focused primarily on ensuring access to respiratory protection in occupational settings characterized by well-defined hazards and employer-employee relationships. With this narrow regulatory focus, the respiratory protection needs of the public and many workers are not being met. As climate change increases the incidence and severity of wildfires, hurricanes, floods, infectious disease outbreaks, and other phenomena that impact air quality and human health, it is imperative that the United States ensure that the respiratory protection needs of the public and all workers are met. Recognizing the urgent need to address the gaps in the nation's ability to meet the respiratory protection needs of the public and workers without workplace respiratory protection programs, this report makes recommendations for a framework of responsibilities and authorities that would provide a unified and authoritative source of information and effective oversight for the development, approval, and use of respiratory protection.
Keywords: Health and Medicine

Implications of the California Wildfires for Health, Communities, and Preparedness: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
California and other wildfire-prone western states have experienced a substantial increase in the number and intensity of wildfires in recent years. Wildlands and climate experts expect these trends to continue and quite likely to worsen in coming years. Wildfires and other disasters can be particularly devastating for vulnerable communities. Members of these communities tend to experience worse health outcomes from disasters, have fewer resources for responding and rebuilding, and receive less assistance from state, local, and federal agencies. Because burning wood releases particulate matter and other toxicants, the health effects of wildfires extend well beyond burns. In addition, deposition of toxicants in soil and water can result in chronic as well as acute exposures. On June 4-5, 2019, four different entities within the National Academies of Sciences, Engineering, and Medicine held a workshop titled Implications of the California Wildfires for Health, Communities, and Preparedness at the Betty Irene Moore School of Nursing at the University of California, Davis. The workshop explored the population health, environmental health, emergency preparedness, and health equity consequences of increasingly strong and numerous wildfires, particularly in California. This publication is a summary of the presentations and discussion of the workshop.
Keywords: Health and Medicine

Global Sources of Local Pollution: An Assessment of Long-Range Transport of Key Air Pollutants to and from the United States - National Research Council (The National Academies Press, 2010)
Recent advances in air pollution monitoring and modeling capabilities have made it possible to show that air pollution can be transported long distances and that adverse impacts of emitted pollutants cannot be confined to one country or even one continent. Pollutants from traffic, cooking stoves, and factories emitted half a world away can make the air we inhale today more hazardous for our health. The relative importance of this "imported" pollution is likely to increase, as emissions in developing countries grow, and air quality standards in industrial countries are tightened. Global Sources of Local Pollution examines the impact of the long-range transport of four key air pollutants (ozone, particulate matter, mercury, and persistent organic pollutants) on air quality and pollutant deposition in the United States. It also explores the environmental impacts of U.S. emissions on other parts of the world. The book recommends that the United States work with the international community to develop an integrated system for determining pollution sources and impacts and to design effective response strategies. This book will be useful to international, federal, state, and local policy makers responsible for understanding and managing air pollution and its impacts on human health and well-being.
Keywords: Environment and Environmental Studies

Indoor Exposure to Fine Particulate Matter and Practical Mitigation Approaches: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine; National Academy of Engineering (The National Academies Press, 2022)
Overwhelming evidence exists that exposure to outdoor fine particulate matter (PM2.5) is associated with a range of short-term and chronic health impacts, including asthma exacerbation, acute and chronic bronchitis, heart attacks, increased susceptibility to respiratory infections, and premature death, with the burden of these health effects falling more heavily on underserved and marginalized communities. Although less studied to date, indoor exposure to PM2.5 is also gaining attention as a potential source of adverse health effects, particularly given that Americans spend 90 percent of their lives indoors and indoor PM2.5 levels can exceed outdoor levels. To better understand the sources of indoor PM2.5, the possible health effects of exposure to indoor PM2.5, and engineering approaches and interventions to reduce those exposure risks, the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop, Indoor Exposure to Fine Particulate Matter and Practical Mitigation Approaches, on April 14, 21, and 28, 2021. The workshop focused on exposures that occur in residential and school buildings and on existing and practical mitigation technologies and approaches. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Our world is changing at an accelerating rate. The global human population has grown from 6.1 billion to 7.1 billion in the last 15 years and is projected to reach 11.2 billion by the end of the century. The distribution of humans across the globe has also shifted, with more than 50 percent of the global population now living in urban areas, compared to 29 percent in 1950. Along with these trends, increasing energy demands, expanding industrial activities, and intensification of agricultural activities worldwide have in turn led to changes in emissions that have altered the composition of the atmosphere. These changes have led to major challenges for society, including deleterious impacts on climate, human and ecosystem health. Climate change is one of the greatest environmental challenges facing society today. Air pollution is a major threat to human health, as one out of eight deaths globally is caused by air pollution. And, future food production and global food security are vulnerable to both global change and air pollution. Atmospheric chemistry research is a key part of understanding and responding to these challenges. The Future of Atmospheric Chemistry Research: Remembering Yesterday, Understanding Today, Anticipating Tomorrow summarizes the rationale and need for supporting a comprehensive U.S. research program in atmospheric chemistry; comments on the broad trends in laboratory, field, satellite, and modeling studies of atmospheric chemistry; determines the priority areas of research for advancing the basic science of atmospheric chemistry; and identifies the highest priority needs for improvements in the research infrastructure to address those priority research topics. This report describes the scientific advances over the past decade in six core areas of atmospheric chemistry: emissions, chemical transformation, oxidants, atmospheric dynamics and circulation, aerosol particles and clouds, and biogeochemical cycles and deposition. This material was developed for the NSF's Atmospheric Chemistry Program; however, the findings will be of interest to other agencies and programs that support atmospheric chemistry research.
Keywords: Earth Sciences

A Century of Wildland Fire Research: Contributions to Long-term Approaches for Wildland Fire Management: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Although ecosystems, humans, and fire have coexisted for millennia, changes in geology, ecology, hydrology, and climate as well as sociocultural, regulatory, and economic factors have converged to make wildland fire management exceptionally challenging for U.S. federal, state, and local authorities. Given the mounting, unsustainable costs and difficulty translating existing wildland fire science into policy, the National Academies of Sciences, Engineering, and Medicine organized a 1-day workshop to focus on how a century of wildland fire research can contribute to improving wildland fire management. This publication summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences

The Chemistry of Fires at the Wildland-Urban Interface - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Wildfires in America are becoming larger, more frequent, and more destructive, driven by climate change and existing land management practices. Many of these fires occur at the wildland-urban interface (WUI), areas where development and wildland areas overlap and which are increasingly at risk of devastating fires as communities continue to expand into previously undeveloped areas. Unlike conventional wildfires, WUI fires are driven in part by burning of homes, cars, and other human-made structures, and in part by burning vegetation. The interaction of these two types of fires can lead to public health effects that are unique to WUI fires. This report evaluates existing and needed chemistry information that decision-makers can use to mitigate WUI fires and their potential health impacts. It describes key fuels of concern in WUI fires, especially household components like siding, insulation, and plastic, examines key pathways for exposure, including inhalation and ingestion, and identifies communities vulnerable to exposures. The report recommends a research agenda to inform response to and prevention of WUI fires, outlining needs in characterizing fuels, and predicting emissions and toxicants.
Keywords: Math, Chemistry, and Physics; Earth Sciences; Environment and Environmental Studies